The Affect Heuristic and Risk Perception – Stability Across Elicitation Methods and Individual Cognitive Abilities - Skagerlund, Kenny; Forsblad, Mattias; Slovic, Paul; Västfjäll, Daniel (Frontiers in Psychology, 2020)
The reliance on feelings when judging risks and benefits is one of the most fundamental valuation processes in risk perception. While previous research suggests that the affect heuristic reliably predicts an inverse correlation between risk and benefit judgments, it has not yet been tested if the affect heuristic is sensitive to elicitation method effects (joint/separate evaluation) and to what extent individual differences in cognitive abilities may mediate the risk-benefit correlation. Across two studies we find that 1) the risk-benefit correlation is stable across different elicitation methods and for different domains (e.g., social domain, sensation-seeking domain, health domain, economic domain), and 2) the strength of the inverse correlation is tied to individual cognitive abilities - primarily cognitive reflection ability.